Prevalence of left ventricular diastolic dysfunction in out - patient with type 2 diabetes mellitus. - Shakya, Nirmal (2001)
ABSTRACT: Objective- To study the prevalence of left ventricular diastolic dysfunction in type 2 diabetes mellitus. Design- Cross-sectional study of thirty six consecutive subjects with diabetes mellitus presenting at the diabetic clinic at Bir hospital and a private diabetic clinic at Jamal, Kathmandu. Setting- Type 2 diabetes patients presenting at diabetic clinic of Bir hospital, a tertiary referral central and post graduate teaching hospital of His Majesty's Government of Nepal and private diabetic clinic run by a non Governmental Organization. Main outcome measures- The diagnosis of left ventricular diastolic dysfunction was established by echocardiography. Observations- Thirty six diabetes subjects were included in the study. Sex distribution was equal in the study. Nearly seventy five percent of the study population belonged to the age group of 50-69 years. Nineteen (53%) of the study subjects had left ventricular diastolic dysfunction of whom only one had a pseudonormal pattern of left ventricular filling and the rest had impaired relaxation. Systolic function was normal in all the subjects. Among them eleven (31%) were female and the rest were male. Altogether there were fourteen hypertensive patients among whom only eight had left ventricular diastolic dysfunction. Conclusion- Left ventricular diastolic dysfunction is much more commoner than is thought and is adversely affected by arterial hypertension whose coexistence further impairs left ventricular relaxation. The high prevalence of this phenomenon in this high risk population suggest that screening for left ventricular diastolic dysfunction should be undertaken. Keywords- diastolic dysfunction, Type 2 diabetes mellitus.